THE BARRIERS TO SOCIAL INCLUSION OF PEOPLE WITH DISABILITIES IN THE REPUBLIC OF MOLDOVA - MUNTEANU, Parascovia (Economy and Sociology, 2021)
The social inclusion of people with disabilities is a current area of research. This group of people continues to be marginalized and excluded from the society’s life. This situation is determined by the high level of discrimination and stigmatization, unequal opportunities, physical and attitudinal barriers that predominate in society. More than one billion people with disabilities worldwide, accounting 15% of the world’s population, face social inequality and the authorities’ limited capacities to respond to the needs of the persons with disabilities. In the European Union, about 80 million people live with disabilities and in the Republic of Moldova about 182.0 thousand people, which represent about 5% of the country’s population. This study aims to analyse barriers to social inclusion of people with disabilities from the Republic of Moldova from the perspective of social roles valorisation. The sociological research methods used in this study are statistical data analysis, documentary analysis; sociological survey based on the questionnaire; the focus group; in-depth interview and sociological observation. The main barriers to social inclusion faced by people with disabilities in the Republic of Moldova are: low living standards compared to the general population, non-observance of the general accessibility principle, limited access to social services, education, health and very low participation of people with disabilities on the labour market. Analysis of social inclusion issues identified through research on the views of people with disabilities, service providers and experts will help strengthen the mechanisms for evaluating, monitoring and improving social inclusion policies.